Phytoplankton Diversity and Pollution Index in North Part of Euphrates River, Iraq - A. Ali, Huda; M. Al-Mahdawi, Mahmood (Iraqi Journal of Science, 2023)
This study covered approximately 150 km from the northern part of the Euphrates River in Iraq. Water and phytoplankton samples were monthly collected from six selected stations from April 2013 to March 2014; three stations were distributed within Hadithah Reservoir, while the three others were in the river's inflow. Water physical and chemical parameters and the phytoplankton community structure were analyzed. The most important results of this study were the diagnoses of 355 phytoplankton species belong to eight phylums. Algal class Bacillariophyceae which belong to phylum Ochrophyta was the most qualitative and quantitative dominant in all stations over the study period. The stations within the reservoir were characterized by higher number of genes and species, which led to higher Shannon-Weaver diversity index values in comparison to other stations. Water quality were evaluated by using the mentioned diversity index and Palmer's pollution index, stations 1 which is located in the river before the reservoir were with low levels of pollution; stations 2, 3 and 4, which are located inside the reservoir and station 5 (downstream the reservoir) were likely polluted, while the organic pollution in station 6 was confirmed because it's location close to the sewage discharge. The study concludes that Palmer's pollution index was more accurate than diversity index for the evaluation of water pollution levels.